Azathioprine Treatment in Systemic Lupus Erythematosus: A Double Edged Sword - XIA, Jia; SU, Xiao; CHEN, Wei-wei; HE, Li-qun (IIUM Medical Journal Malaysia, 2015)
Extremely severe pancytopenia induced by low dosage of azathioprine in systemic lupus erythematosus patients is rare. A 40-year-old Chinese female was diagnosed with systemic lupus erythematosus. She suffered worse erythema, oral ulceration, raised erythrocyte sedimentation rate and high anti-dsDNA in August 2013. Then she was initiated on oral azathioprine 50mg/d and extremely severe pancytopenia was seen in September 2013. She was recovered by a series of treatments. Regular monitoring of blood counts is highly recommended to reduce the possible serious myelosuppression induced by azathioprine.